Voltage equalization control algorithm for monitoring and balancing of series connected lithium-ion battery - Hoque M.M.; Hannan M.A.; Mohamed A. (American Institute of Physics Inc., 2023)
Algorithms; Charging (batteries); Electric batteries; Ions; Lithium; Lithium alloys; Lithium-ion batteries; Secondary batteries; Charge equalization; Energy storage systems; Equalization control; Higher efficiency; Individual cells; Series-connected; State of charge; Vehicle applications; Battery management systems